„Gwiazda Jakuba” (Lb 24,17) i jej interpretacje - Kuśmirek, Anna (Verbum Vitae, 2016)
Among the various interpretations of “The Star out of Jacob” (Numbers 24:17), the messianic reading, present in both the Jewish and the Christian traditions, has played an enormous role. The purpose of this study is to review the development of different interpretations of “The Star out of Jacob”, starting from the Masoretic Text of Numbers 24:17, proceeding through the ancient versions, and ending up with the exegesis of the early Church Fathers.